CO2 emissions, economic growth and population density: an analysis of developing economies - Ochoa Moreno, Wilman Santiago (2019)
This paper explores the validity of the Kuznets environmental curve (EKC) hypothesis for 12 countries in Latin America and tests whether there is evidence that a country has reduced carbon dioxide emissions as its income has increased Also, and how it affects the population growth in the CO2 emissions For this a model of fixed effects panel was estimated, where it was obtained that the variations of the logarithm of gross domestic product of each country influence in 0.30 in the variations of the logarithm of the CO2 emissions was also determined that there is a negative relationship between population growth and the logarithm of CO2 emissions, this occurs because in countries or in years where the population decreases, it continues to increase CO2 emissions